Pengembangan Multimedia Berbasis Google Sites dalam Meningkatkan Pemahaman Siswa pada Mata Pelajaran Ekonomi - Aprilya, Aisyah; Mariatun, Ika Lis (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to determine the effectiveness of using Google Sites-based multimedia as a learning medium on students' conceptual understanding in understanding economics lessons. This is motivated by a lack of student motivation to learn due to monotonous learning facilities.Method – This research uses the Research and Development (R&D) method, which is the approach used to develop and test a product. And using the ADDIE development model proposed by Lee Owens, namely Analysis, Design, Development, Implementation, Evaluation. The data collection techniques used were interviews, observation and questionnaires. Testing includes pre-test and post-test assessments to measure students' level of understanding.Findings – The results of this research in the trial, students were given a pre-test with a class average score of 56.43. Meanwhile, the posttest results obtained a percentage score of 83.24. This is proven by the N-Gain Score results which obtained a score of 0.63 in the quite effective category. Thus, it can be concluded that there is a significant influence in the use of Google Sites-based multimedia on students' understanding. Research Implications – This research proves that Google Sites-based multimedia can significantly increase students' understanding of concepts in economics lessons. Attractive learning facilities will make it easier for teachers to convey learning material and students will more easily understand and master the learning material. The implication is that students play a more active role in economic learning activities and are enthusiastic in participating in learning so that learning objectives can be achieved well.